Dik ve Eğik Kesme İşleminin Termomekanik Modellemesi ve Torna İşlemine Uygulanması - Çakır, Esin (Fen Bilimleri Enstitüsü, 2015)
Tornalama, frezeleme, delik delme ve taşlama işlemleri, iş parçasına son şeklin verildiği, en çok kullanılan imalat yöntemlerindendir. Verimliliğin yanında, işlenen parçanın yüzey kalitesi de önemlidir. Bunun için de, kesme parametrelerinin belirlenmesi önemli hale gelmektedir.  Talaşlı imalatta kesme parametrelerinin seçimi, işlenen parçanın yüzey kalitesi ve takım ömrü bakımından önemlidir. Bu parametrelerin seçimini etkileyen en önemli problemlerden bir tanesi ise ısı oluşumudur. Takım ömrü, talaşlı imalatın verimliliğini doğrudan etkileyen bir parametre olduğundan kesme sırasında ortaya çıkan sıcaklıkların belirlenmesi sürecin optimizasyonu açısından oldukça önemlidir. Kesme işleminde üç tane ısı oluşum bölgesi vardır. Bunlar; talaş oluşumu sırasında iş parçasında meydana gelen plastik şekil değişiminden kaynaklanan ısının oluştuğu birincil deformasyon bölgesi, takım ve talaş arasında, talaş yüzeyindeki sürtünmeden kaynaklanan ısının oluştuğu ikincil deformasyon bölgesi ve takım ile iş parçasının işlenen yüzeyi arasındaki sürtünmeden kaynaklanan ısının oluştuğu üçüncül deformasyon bölgesidir. Bu üç bölgede oluşan ısının bir kısmı, takım ve iş parçasının ısı iletim katsayısına bağlı olarak, takıma geçer. Böylelikle difüzyon ve ısıl gerilmelere neden olarak takım aşınmasını tetikler. Özellikle takım-talaş arayüzeyindeki maksimum sıcaklık, takım aşınması ve  ömrünün belirlenmesi açısından önemlidir.   Bu çalışmada dik kesme koşullarında sıcaklık dağılımının hesaplanması için takım-talaş arayüzeyindeki yapışma ve kayma sürtünme durumuna odaklanarak analitik bir model geliştirilmiştir. Geliştirilen modelde birincil kayma bölgesi ve takım-talaş arayüzeyindeki ısı oluşumu dikkate alınmıştır. Bu modelde, birincil deformasyon bölgesindeki malzeme modeli Johnson-Cook bünye denklemi ile ifade edilmiştir. Takım-talaş arayüzeyindeki sıcaklık dağılımı, iki boyutlu ve zamandan bağımsız olarak modellenmiştir. Sabit ısı dağılım oranı ile bu bölgede oluşan ısının %25’inin takıma geçtiği kabul edilerek, takım ve talaş içerisindeki sıcaklık dağılımları iki boyutlu olarak hesaplanmıştır. Talaş içerisindeki sıcaklık dağılımı için; talaş üst yüzeyindeki ve birincil deformasyon bölgesi çıkışındaki sıcaklığın sabit olduğu kabul edilmiştir. Ayrıca talaş hızı yönünde ısı iletimi ihmal edilmiştir. Takım içerisindeki sıcaklık dağılımı, kutupsal koordinatlarda iki boyutlu Laplace denklemi ile sonlu farklar yöntemi ile bulunmuştur. Takım serbest yüzeyindeki sınır şartı taşınım olarak kabul edilmiştir. Analitik modelden elde edilen sonuçları doğrulamak ve çeşitli koşullarda kesme sıcaklığını belirlemek amacıyla bir deney düzeneği tasarlanmıştır. Deneylerde temassız bir ölçüm yöntemi olan termal kamera kullanılmıştır.  Termal kamera ile yapılan deneyler ile hem literatürdeki verilere hem de geliştirilen model ile hesaplanan değerlere uygun sonuçlar elde edilmiştir. Talaşlı imalatta kesme sıcaklıklarının elde edilmesinin zorluğu düşünüldüğünde elde edilen sonuçlar oldukça tatminkardır.  Bu çalışma ile elde edilen veriler temel alınıp, geliştirilen model eğik kesme şartlarına ve AISI 1050 çeliğinin  tornalama işlemine  uygulanarak doğrulanmıştır. Böylece geliştirilen model ile endüstride kullanılan kesme işlemleri için; maksimum kesme sıcaklığı tahmin edilerek daha verimli kesme sağlayacak parametrelerin seçimine olanak sağlamıştır.

Turning, milling, drilling and grinding are the most common machining processes for producing final shapes in manufacturing. Beside productivity, part quality is very important too. To achieve this, optimizing the parameters becomes significant subject.  Being one of the most important problems in machining is  the heat generation which affects selection of cutting parameters. There are three heat generation regions in the cutting process. Plastic deformation in primary shear zone, friction at secondary shear zone and friction between tool and workpiece at third defrmation zone. Depending on the thermal conductivity of the tool and the workpiece, a portion of the heat is transfers to the tool and causes diffusion and thermal stresses which trigger tool wear. Cutting temperatures, especially maximum temperature at tool-chip interface is very important for the tool life. Thus, temperature in machining is an important issue which is the topic of this thesis.  The aim of this thesis is to develop an analytical thermal model to predict cutting temperatures. Thesis consists of temperature distribution in chip and tool in orthogonal cutting and adoptation of this model to oblique cutting and turning process.  In this study, an analytical model is developed in order to calculate the temperature distribution in orthogonal cutting with dual-zone contact at the rake face. The study focuses on heat generation at the primary shear zone and at the rake face. The material behavior at the primary shear zone is represented by Johnson-Cook constitutive equation whereas the contact at the rake face is modeled by sticking and sliding friction zones. This new temperature distribution model allows obtaining the maximum temperature at the rake face and helps determining two dimensional temperature distribution in the chip and tool. The simulation results obtained from the developed model are also compared with experimental results where good agreement is observed. Firstly, thermal model is developed for orthogonal cutting conditions. Heat generation model in primary deformation zone is that the workpiece material is isotropic, rigid and under shear conditions its thermomechanical behaviour is expressed by Johnson-Cook material model. It is assumed that the chip is formed by shearing in a narrow straight band of thickness whose inclination with respect to the workpiece surface is defined by the shear angle. It is supposed that the material is deformed by shearing in the shear band and that no deformation occurs before and after the band. The secondary shear zone that appears along the tool interface is not considered in the present modelling. The complex material  flow near the tool is not accounted for either. It is assumed the model in primary shear zone is restricted to the case of stationary flow. The uncut chip thickness is presumed to be small with respect to the width of cut. It is then justified to consider that the chip is formed under plane strain conditions. The cutting edge is taken as perfectly sharp and the tool is not deformable. The cutting conditions are given it means that the feed, the rake angle and the cutting speed are known. The location of the maximum temperature also changes with the rake angle. The maximum temperature location, with respect to the tool tip, decreases with the increasing rake angle, meaning that as the rake angle increases the maximum temperature location gets closer to the tool tip.  Although this behaviour cannot be explained as explicitly as the previous behaviour, it is known that the sticking contact length / total contact length ratio decreases as the rake angle increases. This mechanism shifts the normal and shear stress distributions closer to the tool tip, where high values of the stresses have more impact. Therefore, the higher heat generation exists at locations closer to the tool tip.   In the present study, two dimensional and time independent heat transfer model is developed for the temperature distribution in the chip for orthogonal cutting. Heat effects on the primary and secondary shear zones are considered where the material behaviour in the primary shear zone is expressed using the Johnson-Cook material model. Since the model is analytical the solution times are quite short. The model predictions are compared with the cutting temperature data taken from literature. In general, good correlation is obtained with the experimental data for the maximum temperatures. In addition, several simulations such as effect of rake angle on maximum temperature are also done to show the applications of the model in process analysis.  Developed model in this study is applied to oblique cutting and turning process. So effects of inclination angle and nose radius can be analysed.
Thermomechanical Modeling Of Orthogonal And Oblique Cutting With Turning Validation
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Talaşlı imalat; dik kesme; ısı modeli; sıcaklık dağılımı; Machining; orthogonal cutting; thermal model; temperature distribution